Infektionen als Ursache für Fieber unklarer Genese - Salzberger, Bernd; Birkenfeld, Gabriele; Iberer, Michael; Hitzenbichler, Florian (DMW - Deutsche Medizinische Wochenschrift, 2017)
Fever of unexplained (or unknown) origin (FUO) remains a relevant clinical problem even with modern diagnostic methods. In addition to the classical definition, new categories of FUO describe different clinical situations: nosocomial FUO, FUO in neutropenic/immundeficient patients and FUO in patients with HIV-infection. The new categories are defined by much shorter duration of fever, i. e. mostly three days. Each category of FUO shows a different spectrum of infectious diseases. Often, subacute bacterial endocarditis is very difficult to verify. In many cases, patients in intensive care suffer from FUO caused by reactivation of CMV. In patients with HIV the most important diagnostic indicator concerning the origin of infection is the degree of immundeficiency. Biological and nuclear medical (PET-CT) verification procedures have been established in diagnostics. A national or international register should be created with the purpose of data transfer and validation of strategies concerning the treatment of FUO.
Keywords: Fieber unklarer Genese; nosokomiale Infektionen; Infektionen bei immunkompromittierten Patienten; HIV-Infektion; Immunrekonstitutionssyndrom